Government Initiatives to Empower Small and Medium Enterprise: Comparing One Stop Shop for Licensing in Indonesia and Australia - Bhinekawati, Risa (JAS (Journal of ASEAN Studies), 2016)
This article analyzes the initiatives taken by both Indonesian and Australian governments in undertaking bureaucratic reform to support small and medium enterprises.Â  The focus is on how government harmonizes bureaucracy and regulations to empower small medium enterprise in starting, operating, and growing their business. Â Â One of the key initiatives in the two countries is to streamline business regulations and licensing through a single portal so called â€œone stop shop for licensingâ€.Â  Both Indonesia and Australia have started such initiatives almost at the same time, in 2006 and 2008 respectively. Until recently, the two countries have made important progresses but with different approaches.Â  In Indonesia, the objective of the one stop shop is to provide easiness for companies to start the business; while in Australia, the purpose is broader and more comprehensive, which is to achieve â€œseamless Australian economyâ€.Â  This study was conducted in Canberra and Queanbeyan, Australia.Â  The research has found important key lessons from Australia that may be applicable to Indonesia in establishing mechanisms for government initiatives to better support small and medium enterprise through a single portal or one stop shop for licensing.